2015
DOI: 10.4238/2015.december.16.26
|View full text |Cite
|
Sign up to set email alerts
|

Association of single nucleotide polymorphisms in the CYP1B1 gene with the risk of primary open-angle glaucoma: a meta-analysis

M Li2,
et al.

Abstract: ABSTRACT. Mutations in the CYP1B1 gene were detected in primary openangle glaucoma (POAG) patients. However, the association between these mutations and the incidence of POAG remains to be elucidated. Here, we have conducted a meta-analysis to analyze this correlation, using relevant studies obtained from an extensive search of various electronic databases, including EMBase, Web of Science, and PubMed. The extracted studies were selected for the meta-analysis based on the inclusion and exclusion criteria. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“… 1 However, two meta-analysis studies have found no association between CYP1B1 variants and POAG. 9 , 10 In accordance with these studies, our study also reports a negative association between CYP1B1 and POAG.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 1 However, two meta-analysis studies have found no association between CYP1B1 variants and POAG. 9 , 10 In accordance with these studies, our study also reports a negative association between CYP1B1 and POAG.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding supports the conclusion reached by the recently conducted meta-analysis studies. 9 , 10 However, as with other complex diseases, including POAG, large sample numbers are needed to ensure sufficient power to identify the underlying genetic causal effect which may be a limiting factor in this study; besides, the presence of rare variants cannot be ruled out in this study, and as such, these findings need further validation in a larger cohort.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, ER polymorphisms may affect the physiological functions of estrogen in regulating aromatase and its product which later contributes to the development of OAG. Another possibility is that cyp1b1 (cytochrome P450 1B1) is regulated by ER [41], and the downregulation of this gene is correlated with OAG and oxidative stress in TM [42,43], although conflicting results regarding the role of polymorphism in cyp1b1 and the risk of OAG between studies were documented [40,42,44,45]. However, the loss of function in cyp1b1 variants, particularly c.1064_ 1076del, p.(Arg355Hisfs*69), seems to be associated with an increased risk for OAG [45].…”
Section: Discussionmentioning
confidence: 99%
“…In sensitivity analysis, we first excluded reports with fewer than 7 stars in the Newcastle Ottawa Scale assessment (eTable 1 in Supplement 1) 13,27 or cohorts deviating from Hardy-Weinberg Equilibrium in controls, 20,21,[49][50][51] then sequentially omitted each study 1 at a time and recalculated the pooled effect sizes. No significant alterations were observed, suggesting that the results were robust (data not shown).…”
Section: Association Of Primary Angle-closure Diseasementioning
confidence: 99%